Anxiety Levels Of Nurse Profession Students During The Pandemic Covid-19 In Doing Nursing Practices At Santa Elisabeth Hospital Medan In 2021 - Rotua Elvina Pakpahan (Institute of Computer Science (IOCS), 2021)
Anxiety is an emotional condition with a feeling of discomfort in a person, and is a vague experience accompanied by feelings of helplessness and uncertainty caused by something that is not yet clear. The research design is a descriptive design with a cross sectional design method. The sampling technique used was total sampling technique with a total sample of 84 people. The results showed that the level of anxiety in the mild category was 36 respondents (42.9%), in the moderate category as many as 47 respondents (56%), in the severe category as many as 1 respondent (1.2%). Based on the result of the study, it was found that the anxiety level of the majority of respondents was at a moderate level of anxiety, namely experiencing worry, anxiety or nervousness, rising blood pressure, easily tired and feeling muscle and neck pain.